PENGARUH APLIKASI TIKTOK TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI INTERAKSI SOSIAL DI SD N 08 PALEMBANG - Apriani, Kurnia Ayu (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This research aims to analyze the influence of the TikTok application on students’ interest in learning in science subjects, especially social interaction material, at SD Negeri 08 Palembang. The research uses a True Experimental Design approach with a Posttest-Only Control Design. The population, namely fourth grade students at SD Negeri 08, amounted to 58 students who were selected as research subjects using random sampling techniques. The sample was divided into two groups, namely Class IVA (control) which used traditional learning methods and Class IVB (experiment) which applied the TikTok application as a learning medium. Data collection was carried out through normality, homogeneity and hypothesis tests to measure students’ interest in learning and social interactions. The research results show that the use of the TikTok application significantly influences students’ learning motivation in understanding science material, as well as improving the quality of social interaction in the experimental class compared to the control class. TikTok as a learning medium has proven effective in creating a more interesting and interactive learning atmosphere, especially through visual content and creative approaches that are relevant to student characteristics. This research provides important implications for the development of digital technology-based learning methods in elementary schools. Applications like TikTok can be integrated strategically to increase learning motivation while strengthening students’ social interactions in the learning environment. ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh aplikasi TikTok terhadap minat belajar siswa pada mata pelajaran IPAS, khususnya materi interaksi sosial, di SD Negeri 08 Palembang. Penelitian menggunakan pendekatan True Experimental Design dengan desain Posttest-Only Control Design. Populasi yaitu siswa kelas IV SD Negeri 08 berjumlah 58 siswa yang dipilih sebagai subjek penelitian melalui teknik random sampling. Sampel dibagi menjadi dua kelompok, yaitu Kelas IVA (kontrol) yang menggunakan metode pembelajaran tradisional dan Kelas IVB (eksperimen) yang menerapkan aplikasi TikTok sebagai media pembelajaran. Pengumpulan data dilakukan melalui uji normalitas, homogenitas, dan hipotesis untuk mengukur minat belajar dan interaksi sosial siswa. Hasil penelitian menunjukkan bahwa penggunaan aplikasi TikTok secara signifikan memengaruhi motivasi belajar siswa dalam memahami materi IPAS, sekaligus meningkatkan kualitas interaksi sosial di kelas eksperimen dibandingkan dengan kelas kontrol. TikTok sebagai media pembelajaran terbukti efektif dalam menciptakan suasana belajar yang lebih menarik dan interaktif, terutama melalui konten visual dan pendekatan kreatif yang relevan dengan karakteristik siswa. Penelitian ini memberikan implikasi penting bagi pengembangan metode pembelajaran berbasis teknologi digital di sekolah dasar. Aplikasi seperti TikTok dapat diintegrasikan secara strategis untuk meningkatkan motivasi belajar sekaligus memperkuat interaksi sosial siswa di lingkungan pembelajaran.